Peroral cholangioscopy by SpyGlass DS versus CHF-B260 for evaluation of the lateral spread of extrahepatic cholangiocarcinoma - Kanno, Yoshihide; Koshita, Shinsuke; Ogawa, Takahisa; Masu, Kaori; Kusunose, Hiroaki; Sakai, Toshitaka; Murabayashi, Toji; Haegawa, Sho; Kozakai, Fumisato; Yonamine, Keisuke; Kawakami, Yujiro; Fujii, Yuki; Horaguchi, Jun; Noda, Yutaka; Ito, Kei (Endoscopy International Open, 2018)
Background and study aims A newly developed peroral cholangioscopy (POCS) system, SpyGlassDS has high maneuverability. This study aimed to evaluate acceptability of the accuracy of SpyGlassDS accompanied by simultaneous POCS-guided biopsy compared with that of a traditional POCS scope, CHF-B260, to diagnose the lateral extent of extrahepatic cholangiocarcinoma (LEC).Patients and methods Patients who underwent surgical resection after preoperative examinations to diagnose LEC were evaluated. POCS by CHF-B260 was performed if there was discrepancy between preceding fluoroscopy-guided biopsy findings and other examinations between January 2004 and September 2015 (group A, n = 56); and POCS plus POCS-guided mapping biopsy by SpyGlassDS was performed in all surgical candidates between October 2015 and December 2017 (group B, n = 20). The main outcome measure was the accuracy of overall preoperative diagnosis (OPD) of LEC defined based on all examinations, including POCS.Results Accuracy of OPD for the liver side and the ampullary side was 93 % and 100 %, respectively, in group A, and 84 % and 100 %, respectively, in group B (P = 0.37 for the liver side; P, not available for the ampullary side). Diagnostic accuracy of simple optical evaluation by POCS for the liver side and the ampullary side was 83 % and 100 %, respectively, in group A, and 58 % and 88 %, respectively, in group B (P = 0.29 for the liver side; P = 0.40 for the ampullary side).Conclusions POCS by SpyGlassDS was found to be acceptable and could be a standard approach for diagnosis of LEC.